2019
DOI: 10.21203/rs.2.10457/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional status of tuberculosis patients, a comparative cross-sectional study.

Abstract: Background Each year, more than 13.7 million people became an active case of tuberculosis and more than 1.5 million cases of TB patient will die. The association between TB and malnutrition is bi-directional, TB leads the patient to malnutrition, and malnutrition increases the risk of developing active TB by 6 to 10 times. Improving the nutrition of individual greatly reduces tuberculosis. The aims of this study were to assess the nutritional status and determinants of underweight among TB patients.Methods A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…Secondly, nine studies [ 3 , 4 , 15 17 , 19 21 ] reported the detection of H.worm and similarly nine [ 3 , 4 , 11 , 12 , 15 , 16 , 19 21 ] reported T.trichuria . Likewise, S.sterocolaris was reported by eight [ 3 , 4 , 12 , 14 16 , 19 , 20 ] studies. Among intestinal protozoans, G.lamblia was repeatedly reported by seven [ 11 , 12 , 15 , 16 , 19 21 ] studies.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Secondly, nine studies [ 3 , 4 , 15 17 , 19 21 ] reported the detection of H.worm and similarly nine [ 3 , 4 , 11 , 12 , 15 , 16 , 19 21 ] reported T.trichuria . Likewise, S.sterocolaris was reported by eight [ 3 , 4 , 12 , 14 16 , 19 , 20 ] studies. Among intestinal protozoans, G.lamblia was repeatedly reported by seven [ 11 , 12 , 15 , 16 , 19 21 ] studies.…”
Section: Resultsmentioning
confidence: 80%
“…Two hundred sixty-nine studies were screened by title and abstract. Finally, only 20 papers were found to be eligible for full-text evaluation, and 11 studies [ 3 , 4 , 11 , 12 , 14 17 , 19 21 ] that fulfilled the eligibility criteria were included in the final analysis (Table 1 , Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations